Teachers’ Job Satisfaction and Its Perceived Influence on Secondary School Student’s Academic Performance - Olawale Abayomi Onikoyi (Universitas Pendidikan Indonesia (UPI), 2024)
The study investigated the teachers’ job satisfaction and its perceived influence on secondary school students’ academic performance using a descriptive survey research approach. Three research questions and two hypotheses were examined. The population consists of all public secondary school teachers in Ojodu Local Government Area of Lagos State. The study’s sample size comprised 246 teachers selected from eight public secondary schools across the Ojodu Local Government Area of Lagos State using a proportional sampling technique. A self-structured questionnaire regarding Teachers’ Job Satisfaction and perceived influence on secondary school students’ academic performance Questionnaire (TJSPSSSAPQ) was used as the research instrument. Four points Likert scale was used to calculate the respondent’s answers. Descriptive statistic of percentage was utilized to evaluate participant bio-data, percentage and mean were used to address the study issues, and Pearson Product Moment Correlation was employed to test the hypotheses. It was concluded that teachers’ satisfaction with working conditions and human relations significantly correlated with the academic performance of secondary schools in the Ojodu Local Government Area. However, it was recommended that school management and the education board should recognize the effort of teachers and reward them appropriately. They should encourage teachers through regular and prompt payment of salaries, good working conditions, regular promotions, and other welfare packages.